An experimental class proposal in distance learning: Identifying proteins in everyday foods in the discipline of Biochemistry (Research, Society and Development, 2021)
Currently, Distance Education (EaD) has been increasingly widespread, being an important means of teaching. In 2020, with the advent of the new coronavirus pandemic, teaching has been based on distance learning, mainly on virtual teaching platforms (video lessons). Biochemistry is a fascinating area, however, it has several terms and processes that must be very well assimilated and understood, making this discipline complex and challenging to students. Thus, in order to overcome such obstacles, the objective of this work is the proposal of a virtual experimental class with the theme of identification of proteins in different foods of everyday life, using the Biuret reagent, applied to students of higher education courses focused on Biological Sciences courses focused on Health areas. Thus, we believe that with this methodological proposal, virtual classes can become increasingly captivating, motivating students and facilitating their learning, in addition to promoting the perspective of scientific experimentation.